ANALISIS HUBUNGAN PELAKSANAAN PROGRAM MAKAN BERGIZI GRATIS TERHADAP MOTIVASI BELAJAR SISWA MTSN 12 PESISIR SELATAN - Syafti, Okviani; Rahman, Antoni; Maharani, Devina Shafira (STKIP Pesisir Selatan, 2025)
Motivation to learn is important in educational success. Motivation to learn is not only influenced by psychological factors, but also by physical condition, including nutritional intake. More than 50% of MTsN 12 Pesisir Selatan students do not eat breakfast before going to school. This has a negative impact on students' physical and psychological readiness, energy, enthusiasm for learning, activeness and persistence in the learning process at school. As an effort to overcome this problem, the Indonesian government has implemented a Free Nutritious Meal (MBG) program for school children. This research aims to find out whether there is a relationship between the MBG program and the learning motivation of MTsN 12 Pesisir Selatan students. This research uses a quantitative approach with Correlation Analysis and Simple Linear Regression Test. The research population was all MTsN 12 Pesisir Selatan students, with samples selected based on stratified random sampling of 30 students. The research results show that there is a strong and significant positive relationship between the MBG Program and student learning motivation with a value of r = 0.912. This means that the better the implementation of the MBG program, the higher the student's learning motivation